Physical activity and combined hormonal contraception: association with female students’ perception of menstrual symptoms - Bougault, Valérie; Schiano-Lomoriello, Sandrine; Castanier, Carole; Buisson, Corinne; Ericsson, Magnus; Teulier, Caroline; Collomp, Katia (Frontiers in Physiology, 2023)
Aim: The aim of this study was to examine the association between physical activity (PA) and combined hormonal contraception (CHC) on female students’ perception of their menstrual cycle self-perceived symptoms. Methods: Healthy French female students (n=834) completed an online questionnaire to assess their PA level [Group 1: non-active; Group 2: moderate PA; Group 3: high PA; Group 4: very high PA], menstrual status or contraception use, self-reported diet and medication, impact on engagement in some social activities, and self-assessment of perceived mental and physical symptoms during the week prior to menses (PM) for students with a normal menstrual cycle (NMC), and the week of menses (ME) for NMC students and those using CHC. Results: Whatever the conditions (PM and ME, NMC and CHC), fewer self-perceived symptoms and self-reported alteration in fat intake were reported by the students in Group 4, and more analgesic and anti-inflammatory medication use was reported by Group 1. Fewer self-perceived symptoms were also found in CHC vs. NMC female students for all PA levels, but in a more marked way when associated with very high PA. In addition, less university and sports practice absenteeism was observed with high and very high PA. Conclusion: In conclusion, the perception of menstrual cycle symptoms was lower with very high PA, as with CHC. Moreover, female students training more than 5 hours/week also reported less university absenteeism and impairment in physical activities. Further studies are necessary to establish the causal link of PA and CHC on menstrual symptoms.